Linkage conversions in single-crystalline covalent organic frameworks - Yu, Baoqiu; Lin, Rui-Biao; Xu, Gang; Fu, Zhi-Hua; Wu, Hui; Zhou, Wei; Lu, Shanfu; Li, Qian-Wen; Jin, Yucheng; Li, Jing-Hong; Zhang, Zhenguo; Wang, Hailong; et al. (Nature chemistry, 2024)
Single-crystal X-ray diffraction is a powerful characterization technique that enables the determination of atomic arrangements in crystalline materials. Growing or retaining large single crystals amenable to it has, however, remained challenging with covalent organic frameworks (COFs), especially suffering from post-synthetic modifications. Here we show the synthesis of a flexible COF with interpenetrated qtz topology by polymerization of tetra(phenyl)bimesityl-based tetraaldehyde and tetraamine building blocks. The material is shown to be flexible through its large, anisotropic positive thermal expansion along the c axis ( α c = +491 × 10 –6 K –1 ), as well as through a structural transformation on the removal of solvent molecules from its pores. The as-synthesized and desolvated materials undergo single-crystal-to-single-crystal transformation by reduction and oxidation of its imine linkages to amine and amide ones, respectively. These redox-induced linkage conversions endow the resulting COFs with improved stability towards strong acid; loading of phosphoric acid leads to anhydrous proton conductivity up to ca. 6.0 × 10 −2 S cm −1 . Covalent organic frameworks offer a highly tunable class of materials for a range of applications, although their dynamic structural transformations are challenging to analyse. Now single-crystal X-ray diffraction is shown to demonstrate single-crystal-to-single-crystal transformations of the imine linkages, showing a well-defined interpenetrating topology and affording structures that have high positive thermal expansion and anhydrous proton-conduction properties.